THE EFFECT OF IMPLEMENTING GCG (GOOD CORPORATE GOVERNANCE), WITH GGE (GREEN-GROWTH ECONOMY) AS A MODERATING VARIABLE OF FINANCIAL PERFORMANCE ON INCREASING ECONOMIC INCOME THROUGH GDP/GNP POST-TOWARDS THE NEW NORMAL - Margaretha Prihatiningsih; Yusup Hari Subagyo; Elisabeth Francisca Sibarani; Intan Paska; Felix Ikko (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Research with the title: